Development of an E-Module for Art Performance Based on Integrated Learning at SMAN 1 Jatibarang - Indra Maghfiroh; Hartono Hartono; Wahyu Lestari (Edumaspul: Jurnal Pendidikan, 2025)
The research aims to develop a Project-Based Learning (PjBL)-based art performance learning module integrated with History, Language, Economics, Informatics, as well as Craft and Entrepreneurship subjects. The method employed is Research and Development (R&D) using the ADDIE development model, which consists of the analysis, design, development, implementation, and evaluation stages. The development subjects are Grade XII students at SMA Negeri 1 Jatibarang. Data collection instruments include interview sheets, observation sheets, questionnaires, student worksheets, expert validation sheets, and documentation. Data analysis is conducted using descriptive statistical analysis techniques. The module development is designed to enhance students’ collaborative skills, creativity, and interdisciplinary understanding. The module validation is carried out by subject matter experts, media experts, and peers, with limited trials conducted on students. The findings indicate that the developed module meets validity and effectiveness criteria based on expert assessments and positive student responses. The development of the art performance module is expected to serve as an innovative learning alternative that supports the Merdeka Curriculum.